2013
DOI: 10.3141/2339-10
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Annual Average Daily Bicyclists

Abstract: Cities around the United States are investing in bicycle infrastructure, and to secure additional transportation funding, cities are reporting bicycle use and safety improvements. Data on bicyclist traffic volume is necessary for performing safety studies and reporting facility use. Meeting the need for data, available manual bicycle counting programs count cyclists for a few hours per year at designated locations. A key issue in the design of counting programs is determining the timing and frequency of counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 1 publication
1
57
0
Order By: Relevance
“…Ridership data are difficult to obtain and often limited by traditional methods of data collection (Gosse and Clarens, 2014;Nordback et al, 2013). Traditional data collection methods typically include manual counts of cyclists during peak commuting periods, which are adjusted to provide an estimate of overall ridership.…”
Section: Introductionmentioning
confidence: 99%
“…Ridership data are difficult to obtain and often limited by traditional methods of data collection (Gosse and Clarens, 2014;Nordback et al, 2013). Traditional data collection methods typically include manual counts of cyclists during peak commuting periods, which are adjusted to provide an estimate of overall ridership.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts typically involve establishment of a set of permanent automated counters at a fixed number of locations believed to represent specific traffic patterns and then collection of a large number of short-duration (e.g., two to seven day) samples that can be used to characterize flows on a network. Statistics and ratios from the permanent sites are used to extrapolate the sample counts and obtain estimates of daily traffic (Federal Highway Administration, 2013;El Esawey, Lim, Sayed, & Mosa, 2013;Miranda-Moreno, Nosal, Schneider, & Proulx, 2013;Nordback, Marshall, Janson, & Stolz, 2013;Hankey, Lindsey, & Marshall, 2014). Several studies of trail use using these technologies and monitoring approaches have been reported (e.g., Lindsey, Wilson, Rubchinskaya, Yang, & Han, 2007;Wang, Lindsey, Hankey, & Hoff, 2014).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Emerging research focuses on describing patterns of bicycle and pedestrian traffic on transportation networks—for example, designing traffic count programs (Hankey et al 2014; Nordback et al 2013) and building facility–demand models (Hankey and Lindsey 2016; Miranda-Moreno and Fernandes 2011; Schneider et al 2012). Those findings highlight research and policy questions about how best to provide safe, health-promoting infrastructure for active travel (Loukaitou-Sideris et al 2014; McDonald et al 2014; Wilson et al 2010).…”
Section: Introductionmentioning
confidence: 99%